The Kansas State Honor Flute Choir - White, Chelsea M. (My University, 2015)
The Kansas State Honor Flute Choir is an ensemble of flute players in grades 5- 12. The ensemble was auditioned and led by Dr. Karen Large and myself. The purpose of creating this ensemble was to engage flute players in the Manhattan area an the surrounding communities and challenge these students to explore aspects of the flute that are outside the regular 5-12 band programs in the state of Kansas. These flute players were challenged to play music of a higher level in an ensemble where they play a different role in the ensemble than in a traditional band. Students also received the opportunity to play other flutes such as the Alto flute and Bass flute. This experience was culminated by a final concert. This project took place in the spring semesters of 2014 and 2015. We worked to market the ensemble and well as adjust our expectations for the ensemble throughout the course of these two years. We began each year by picking repertoire that was at a level achievable by students of a grade level that we had determined would make up most of the choir. We planned rehearsals and the concert based on what the students had achieved. This program was also a learning experience for me. I was the Assistant Director to this program and this experience was structured to give me an opportunity to conduct a flute choir, lead rehearsals to teach music in a timely manner and to aid my teaching. During this project we also planned to have me perform a solo with the flute choir and perform an arrangement of a Disney song for the younger students. Additional performances included a performance at the Kansas State University Flute Day.